N‐Benzyldithiocarbamate Salts as Sulfur Sources to Access Tricyclic Thioheterocycles Mediated by Copper Species. Issue 17 (3rd August 2016) - Luo, Bingling; Cui, Qingbin; Luo, Hongwen; Hu, Yumin; Huang, Peng; Wen, Shijun
Abstract: Using an easily prepared triethylammonium N ‐benzyldithiocarbamate salt as a sulfur source, a dual C−S functionalization of cyclic diaryliodoniums to form tricyclic thioheterocycles is realized. Our method uses the readily available copper sulfate to accelerate the chemical transformation under mild conditions. A broad range of cyclic diaryliodoniums with a ring size from 5‐ to 7‐membered can be employed to gain a quick access to tricyclic thioheterocycles including dibenzothiophenes, thioxanthenes, and phenoxathiines. Abstract :